The relationship of simplified acute physiology score 3 (SAPS 3) and C-reactive protein (CRP) levels with mortality rates and length of stay of patients in surgical intensive care unit - Mungan, İbrahim; Turan, Sema; Kazancı, Dilek; Cankar Dal, Hayriye; Yamanyar, Serdar; Sevim Yakın, Sultan; Bostancı, Erdal Birol (The European Research Journal, 2019)
Objectives: The individual risk of surgical patients is more often underestimated and < 15% of patients who underwent surgery were admitted to ICU. The prognostic scores were developed to assess the mortality rate and prognosis for critical patients including surgical ones. The Acute Physiology and Chronic Health Evaluation (APACHE) score and the Simplified Acute Physiology Score (SAPS) were most popular ones and they were revised with the improvements in health care opportunities. As a prognostic scoring system SAPS 3’ results were defined as excellent in high risk surgical patient study group. CRP is useful as a prognostic indicator or an index of disease progression but its value has not been tested in acute settings adequately. The aim of this study is to test the calibration power of SAPS 3 score and identify correlations between hospital mortality and patient outcomes with SAPS 3 scores and CRP levels.Methods: This retrospective and analytical study was conducted one year period in surgical ICUs of tertiary level of attention in a public institution. It was a case–control medical record review and the patients included in this study were those who admitted in the surgical ICU for any reason.Results: A total of 806 patients admitted to the Gastroenterological surgical ICU was included in the study between March 2016 and March 2017. The relation between mortality rate, length of stay in ICU and SAPS 3 score was significant statistically and the relation of CRP levels with SAPS score and mortality rate was found significant statistically. Conclusion: The discriminative power of SAPS 3 score was very good and the calibration was appropriate.